A dual-functional biomimetic-mineralized nanoplatform for glucose detection and therapy with cancer cells in vitro. Issue 18 (30th April 2021) - Yang, Chunlei; Gao, Mengxu; Zhao, Hengzhi; Liu, Yazhou; Gao, Na; Jing, Jing; Zhang, Xiaoling
Abstract : A smart pH responsive dual-functional biomimetic and mineralized nanoplatform was designed for glucose detection in serum samples and therapy with tumor cells. Abstract : Glucose detection is a crucial topic in the diagnosis of numerous diseases, such as hypoglycemia or diabetes mellitus. Research indicates that people with diabetes mellitus are at a higher risk of developing various types of cancer. A nanoplatform that combines both diabetes diagnosis and cancer therapy might be regarded as a more effective way to solve the above-mentioned problem. However, none of the known sensors has a smart strategy that can work as a fluorescent glucose sensor and a cancer therapeutic platform simultaneously. Here, we developed a pH responsive biomimetic-mineralized nanoplatform (denoted as CaCO3 -PDA@DOX-GOx) for glucose detection in serum samples and applied it to treat the tumor cells combined chemotherapy with the starvation therapy in vitro . Doxorubicin (DOX) and glucose oxidase (GOx) were loaded through the mesoporous CaCO3 -PDA nanoparticles (m-CaCO3 -PDA NPs). The fluorescence of DOX is quenched as a result of fluorescence resonance energy transfer (FRET) caused by the broad absorption of m-CaCO3 -PDA NPs. The nanoplatform would recover fluorescence under lower pH values due to the catalytic reaction of GOx with glucose or tumor microenvironment (TME), which leads to the elimination of FRET. Its application as a glucose sensor is indicated with a linear relationship in the range of 0.01–1.0 mM of glucose and limit of detection is calculated by 6 μM. This nanoplatform also has a TME-responsive antitumor effect and fluorescence imaging functionality, which provide a new idea for cancer therapy together with glucose monitoring in diabetes.